Improving the Economic Mechanism for Increasing the Efficiency of Service Enterprises - Mullayeva Mexrangiz Axtam Qizi (Academia Open, 2026)
General Background: The service sector is a major driver of economic growth, employment, and structural transformation in modern economies. Specific Background: In the Samarkand region, service enterprises have expanded significantly during 2015–2024, supported by institutional reforms, digitalization, and growing demand for services. Knowledge Gap: Despite positive growth, challenges remain, including uneven infrastructure, limited financial resources, low technological modernization, and human capital constraints, indicating the absence of an integrated economic mechanism for improving efficiency. Aims: This study aims to analyze development trends and propose a scientifically grounded economic mechanism model to improve service enterprise efficiency. Results: The findings show more than fivefold growth in service volume, increased employment, rising labor productivity, and expanding digital services. Key determinants include institutional support, financial accessibility, infrastructure development, digital transformation, and human capital. Novelty: The study develops a comprehensive economic mechanism model integrating state regulation, market processes, innovation, and digital transformation to optimize service enterprise performance. Implications: The proposed model provides a foundation for regional economic policy, supporting productivity growth, service quality improvement, and balanced regional development in the service sector. Highlights:• Service Output Expanded Over Fivefold Alongside Rising Workforce Participation• Digital Adoption and Infrastructure Expansion Linked to Productivity Gains• Integrated Framework Combining Policy, Innovation, and Enterprise Systems Proposed Keywords: Service Sector, Service Enterprises, Economic Efficiency, Digital Transformation, Regional Development.